2018
DOI: 10.1017/s0025100318000063
|View full text |Cite
|
Sign up to set email alerts
|

Sasak, Meno-Mené dialect

Abstract: Sasak is a Malayo-Sumbawan (Adelaar 2005) language spoken as a primary language in Lombok, Indonesia (see the map in Figure 1). It is estimated to be spoken by 2 million (Clynes 1995) or 2.5 million (Marli 2015) people. Sasak is reported to have four (Jacq 1998) or five (Austin 2003) major dialects, to which Austin (2003) gives informal names based on the pronunciation of the deictic words for ‘like this’ and ‘like that’: Ngenó-Ngené (central northeast, central east, and central west coasts of Lombok), Menó-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Rather, all influence on vowel quality derives from the stress on the syllable in which it occurs, which according to the authors falls largely on the final syllable. Like Chahal (1998), Archangeli et al (2018) find that vowels occupy a smaller acoustic space in unstressed (i.e. pre-final) syllables than they do in stressed (i.e.…”
Section: Previous Workmentioning
confidence: 58%
See 3 more Smart Citations
“…Rather, all influence on vowel quality derives from the stress on the syllable in which it occurs, which according to the authors falls largely on the final syllable. Like Chahal (1998), Archangeli et al (2018) find that vowels occupy a smaller acoustic space in unstressed (i.e. pre-final) syllables than they do in stressed (i.e.…”
Section: Previous Workmentioning
confidence: 58%
“…Because of the observed relationship between stress and vowel quality in Meno-mene Sasak it is necessary to explore stress's potential relationship to the current data (Chahal 1998, Archangeli et al 2018). Yet, this is not a straightforward discussion; stress has been an engaged area of investigation among Indonesian languages due to its high degree of variability within the region (Goedemans & van Zanten 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of commoner variations is widely can be found in daily communication in sasak. This commoner variation are considered more flexible and contains various vocabularies differences than in noble one (Zain et al, 2022;Archangeli et al, 2020). In fact, the research found that the vocabulary to address the word "eat" can be "medaran" "medahar" in noble class.…”
Section: Discussion Language Variations Reflects Class In Sasakmentioning
confidence: 99%